2015
DOI: 10.1148/rg.2015140267
|View full text |Cite
|
Sign up to set email alerts
|

CT Dose Optimization in Pediatric Radiology: A Multiyear Effort to Preserve the Benefits of Imaging While Reducing the Risks

Abstract: The marked increase in radiation exposure from medical imaging, especially in children, has caused considerable alarm and spurred efforts to preserve the benefits but reduce the risks of imaging. Applying the principles of the Image Gently campaign, data-driven process and quality improvement techniques such as process mapping and flowcharting, cause-and-effect diagrams, Pareto analysis, statistical process control (control charts), failure mode and effects analysis, "lean" or Six Sigma methodology, and closed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 24 publications
0
22
0
3
Order By: Relevance
“…Nevertheless, as the information obtained by MRI and CT is often complementary, our institutional practice includes an MRI examination (if possible without sedation) followed by a low-dose CT protocol to assess bony structures for improved lesion characterization or for presurgical planning. As suggested in the literature [6], the radiation dose delivered by CT should be minimized in accordance to the As Low As Reasonably Achievable (ALARA) principle, in particular as children have a higher risk for expressing radiation effects during their life span than adults [6]. Therefore, whenever CT is needed, the size of the scanned body region should be limited to the minimum necessary and a low-dose protocol should be applied.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…Nevertheless, as the information obtained by MRI and CT is often complementary, our institutional practice includes an MRI examination (if possible without sedation) followed by a low-dose CT protocol to assess bony structures for improved lesion characterization or for presurgical planning. As suggested in the literature [6], the radiation dose delivered by CT should be minimized in accordance to the As Low As Reasonably Achievable (ALARA) principle, in particular as children have a higher risk for expressing radiation effects during their life span than adults [6]. Therefore, whenever CT is needed, the size of the scanned body region should be limited to the minimum necessary and a low-dose protocol should be applied.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…In a recent study from the Mallinckrodt Institute of Radiology, St. Louis Children's Hospital, Washington University School of Medicine, Greenwood et al . report substantial variation in radiation exposure per CT examination, even when repeat studies were performed on the same patient [18]. In this project, investigation into such process variation revealed that multiple age and condition-specific pediatric head CT protocols were available on their institution's two scanners, and that there was more variability on weekends and evenings because less experienced technologists were on duty during these times [18].…”
Section: Discussionmentioning
confidence: 99%
“…report substantial variation in radiation exposure per CT examination, even when repeat studies were performed on the same patient [18]. In this project, investigation into such process variation revealed that multiple age and condition-specific pediatric head CT protocols were available on their institution's two scanners, and that there was more variability on weekends and evenings because less experienced technologists were on duty during these times [18]. Interestingly, in our own study, a similar issue regarding off-hours staffing and variability in CT technologists' level of expertise in protocoling patients on the CH's single CT scanner was articulated by the CH imaging director.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations